Determinants Of Carbon Emissions In G-20 Countries with Financial Development as A Moderation Variable - Hasbi, Hasbi; Wibowo, Muhammad Ghafur (Jurnal Wilayah dan Lingkungan, 2024)
In the last 40 years, the continuous strengthening of the greenhouse effect has led to a significant increase in global average temperatures. Although people's understanding of climate change has improved, the world has not witnessed a significant reduction in pollutant emissions therefore, it is crucial to find the root cause. The purpose of this study is to examine and analyze the effect of trade openness, foreign direct investment, gross domestic product, human capital, industry, financial development on carbon emissions (CO2) in G20 countries during the period 2000-2019. Data analysis was carried out using the Generalized Least Square (GLS) Method model and data processing using the STATA application version 17.0. The results showed that trade openness, gross domestic product, human capital, and industry have a significant effect on carbon emissions (CO2) while foreign direct investment does not have a significant effect. In addition, the Financial Development variable is able to moderate the effect of trade openness, gross domestic product, human capital, industry on carbon emissions (CO2) but on the other hand cannot moderate foreign direct investment. The study's findings contribute to knowledge by providing new evidence on the relationship between financial development metrics and the environment. These findings are crucial for policymakers and relevant authorities to focus on economic development without jeopardizing environmental damage.